Macroeconomics : - Hall, Robert E. (Thomson Delmar Learning, 2005)
Departing from the encyclopedic nature of most Principles texts, which encourages students to simply memorize concepts and see economics as a collection of unrelated terms, formulas, graphs, and theories, this text provides students with a picture of economics as a unified discipline; a set of interrelated tools and ideas that can be used to look at the world in a different way. This book's concise, less is more approach has been carefully crafted in terms of both content and supporting pedagogy to keep students focused on learning and applying the central ideas used in economic analysis. It uniquely employs a simple methodology throughout to emulate how economists look at problems, and teaches students how to use this same analytical process in developing their own economic analysis skills. Hall/Lieberman's careful focus on core theoretical ideas as well as systematically applying the theoretical tools to interesting real-world questions conveys the message that economics is an integrated, powerful body of knowledge that can be used to address important issues.